Occupational and environmental pesticide exposure and associated health risks among pesticide applicators and non-applicator residents in rural Ethiopia - Tessema, Roba Argaw; Nagy, Károly; Ádám, Balázs (Frontiers in Public Health, 2022)
Intensive pesticide use increased concern about the potential acute and chronic health effects of pesticides in general and among applicators in particular. This study aims to explore occupational and environmental pesticide exposure and health risks among pesticide applicators and residents. A community-based cross-sectional study was conducted involving 1,073 individuals. We examined the health effects potentially attributable to pesticide exposure using regression to estimate prevalence ratios (PR). A higher proportion of good knowledge of pesticides [75 vs. 14%; APR = 1.542 (1.358–1.752), p < 0.001] and a higher mean score of perceived health risk of pesticide use [4.21 vs. 3.90; APR = 1.079 (1.004–1.159), p < 0.05] were observed among applicators than residents. A significantly higher proportion of applicators experienced health effects presumably related to pesticide exposure among themselves (36%) than residents (16%), and a higher proportion of them used prescribed drugs in the past 12 months [51 vs. 32%; APR = 1.140 (1.003–1.295), p < 0.05]. Skin irritation, shortness of breath, cough, and dizziness were more likely reported by applicators than residents. Perceived toxicity of currently applied pesticide products, mix pesticides without gloves, regularly maintain and wash sprayer tank after application, occurrence of an incidental splash during mixing and application, and using home-based care after experiencing a symptom presumably due to pesticide exposure were significantly associated with health effects among applicators. Use of face mask and visiting health facility when experiencing a symptom presumably due to pesticide exposure were significantly positively correlated with attending training on the health risks and use of pesticides. A substantial proportion of applicators reported improper use of preventive measures and methods of pesticide waste disposal. These observations point out that applicators can face high health risks of occupational pesticide exposure in Ethiopia. Even trained applicators pursued poor preventive practices; hence, comprehensive practice-oriented in-depth training focusing on safety precautions and proper use of personal protective equipment, and provision of adequate pesticide waste disposal means are crucial interventions.